Pelaksanaan Lelang Eksekusi Hak Tanggungan Melalui Media Internet Masa Pandemi Covid-19 Berdasarkan Undang-Undang Informasi Dan Transaksi Elektronik (Studi Pada KPKNL Medan) - Maryoso, Maryoso; Isnaini, Isnaini; Ramadhan, Muhammad Citra (Mahesa Research Center, 2021)
The Covid-19 pandemic has significantly impacted the economic sector, especially the banking sector in obtaining debt repayments from debtors. To obtain debt repayment from a defaulting debtor, it can be done by selling debt guarantees that have been tied with Mortgage Rights. This study aims to examine and analyze the legal rules, mechanisms and obstacles faced in the implementation of the Mortgage Execution auction through the internet media during the Covid-19 pandemic based on the ITE law. This study uses a normative juridical legal research method with a historical, explanatory and synchronization legal approach using primary, secondary and tertiary legal materials then data analysis is carried out qualitatively. The results of the study show that the auction of Mortgage executions through the internet media during the Covid-19 pandemic based on the ITE law at the Medan KPKNL has been carried out based on applicable law and the resulting auction minutes are valid authentic deeds. However, it is still necessary to improve both in terms of regulations and support systems so that auctions via the internet can be carried out effectively, transparently, accountable, fair, and guarantee legal certainty.